Iodinated polyesters as a versatile platform for radiopaque biomaterials. Issue 13 (2nd May 2017) - Houston, Katelyn R.; Brosnan, Sarah M.; Burk, Laurel M.; Lee, Yueh Z.; Luft, J. C.; Ashby, Valerie S.
ABSTRACT: The design of polymeric biomaterials with long‐lasting X‐ray contrast could advance safe and effective implants and contrast agents. Herein, a new set of wholly aliphatic, iodinated polyesters are synthesized and evaluated as high‐contrast biomaterials and nanoparticle contrast agents for general computed tomography imaging. A single iodinated monomer is used to synthesize a variety of aliphatic polyesters with tunable thermal and mechanical properties. These iodinated polyesters are end‐functionalized with a photocurable methacrylate group, which allows easy processability. The resulting materials exhibit no cytotoxicity and are radiopaque, containing over 40% iodine by weight after processing. The polymers can be formulated into lipid–polymer hybrid nanoparticles using a modified nanoprecipitation method. Initial studies indicate that these nanoparticles show good continual contrast over 60 minutes with no uptake into the kidneys. The work presented here illustrates a novel platform for iodinated polyesters that exhibit high radiopacity and processability, low cost, and no cytotoxicity. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 2171–2177 Abstract : A variety of aliphatic, radiopaque polyesters are synthesized and evaluated using a unique, iodinated monomer. These polymers exhibit high radiocontrast, tunable thermal and mechanical properties, and low cytotoxicity. They can be easily processed into both nanoparticles and thermosets. These nanoparticles show good continual contrast with no uptake into the kidneys. This new platform of radiopaque biomaterials could contribute toward the development of safer, more effective implants and contrast agents.